2019
DOI: 10.1084/jem.20190490
|View full text |Cite|
|
Sign up to set email alerts
|

KLRG1 and NKp46 discriminate subpopulations of human CD117+CRTH2− ILCs biased toward ILC2 or ILC3

Abstract: Recently, human ILCs that express CD117 and CD127 but lack CRTH2 and NKp44 have been shown to contain precursors of ILC1, ILC2, and ILC3. However, these ILCs have not been extensively characterized. We performed an unbiased hierarchical stochastic neighbor embedding (HSNE) analysis of the phenotype of peripheral blood CD117+ ILCs, which revealed the presence of three major subsets: the first expressed NKp46, the second expressed both NKp46 and CD56, and the third expressed KLRG1, but not NKp46 or CD56. Analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
114
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(135 citation statements)
references
References 52 publications
21
114
0
Order By: Relevance
“…From this perspective, Lim et al transferred human CD117 + ILCs into BALB/c Rag2 −/− Il2rg −/− Sirpa NOD (BRGS) mice that are permissive for robust multi-lineage human hematopoietic stem cell engraftment; they found that CD117 + ILCs successfully reconstituted ILCs in various organs (lung, gut, liver, and spleen) [9]. A recent study by Nagasawa et al succeeded in verifying the presence of CD117 + ILC progenitors in peripheral organs (nasal polyps) which correspond to the circulating progenitors, but with limited potential for multi-lineage differentiation [34]. These results imply that circulating CD117 + multipotent ILC progenitors can differentiate into tissueresident ILCs to maintain tissue homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…From this perspective, Lim et al transferred human CD117 + ILCs into BALB/c Rag2 −/− Il2rg −/− Sirpa NOD (BRGS) mice that are permissive for robust multi-lineage human hematopoietic stem cell engraftment; they found that CD117 + ILCs successfully reconstituted ILCs in various organs (lung, gut, liver, and spleen) [9]. A recent study by Nagasawa et al succeeded in verifying the presence of CD117 + ILC progenitors in peripheral organs (nasal polyps) which correspond to the circulating progenitors, but with limited potential for multi-lineage differentiation [34]. These results imply that circulating CD117 + multipotent ILC progenitors can differentiate into tissueresident ILCs to maintain tissue homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…We further identified a third subpopulation that expressed skin homing receptor CCR10 (CCR10 + ILC2s) within c-Kit + ILC2s, which seemed to represent a precursor of skin ILC2s while exhibiting ILC3-like features (2). Peripheral blood CRTH2 − c-Kit + ILCs were once considered to be ILC3s (10), but recent studies have suggested that these populations are highly heterogeneous and contain progenitors for all ILC populations (4,11). Most recent study showed that an NKp46 + population and a KLRG1 + population within blood CRTH2 − c-Kit + ILCs represent progenitors biased toward ILC3s or ILC2s, respectively (4).…”
Section: Introductionmentioning
confidence: 99%
“…Plasticity of ILC precursors and differentiation into ILC2 and ILC3. Nagasawa, et al (2019) identify four subsets of human ILC precursor or progenitor cells based on expression of KLRG1 and NKp46, highlight discriminating transcription factors in the populations, and demonstrate their plasticity when stimulated with DL1 and polarizing cytokine environments.…”
mentioning
confidence: 99%
“…In this issue of JEM , Nagasawa, et al (2019) analyze the subset of human CD127 + lymphocytes lacking mature “lineage” markers isolated from blood, tonsil, and nasal polyps. Starting with a population expressing CD117 that has previously been suggested to contain ILC progenitor populations, unsupervised clustering based on multidimensional flow cytometry analysis revealed three subsets: one characterized by expression of NKp46 and CD56, another by expression of KLRG1, and a third lacking NKp46 and KLRG1 and CD56 +/− .…”
mentioning
confidence: 99%
See 1 more Smart Citation